2015
DOI: 10.1080/09712119.2015.1021810
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different amounts of field peas (Pissum sativumL.) in the diets for turkeys on meat qualities

Abstract: A study was carried out to determine the efficiency of soybean oil meal replacement with increasing amount of peas (from 10% to 40%) in the diets for turkeys on anatomic carcass dissection and chemical indicators of breast, shoulder, thigh and shin muscles, physical indicators of breast muscles and the content of tryptophan and oxyprolin. The anatomic dissection of carcasses indicated that male turkeys fed peas had from 0.28% to 0.61% (P > 0.05-P < 0.05) less shoulder muscles, whereas female turkeys of the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…On the contrary, our data on the oxyprolin content partly in female breast and male thigh muscles contradicts the findings of Barroeta (2007) who noticed that the composition of the feed has no influence on the amino acid content in poultry meat and also do not agree with the results of Leikus et al (2004); Leikus (2006);and Juodka et al (2016) who indicated that the use of lupine or peas in the feed had no effect on the oxyprolin content in meat.…”
Section: Effects Of Different Amounts Of Blue Lupine (L Angustifoliucontrasting
confidence: 57%
“…On the contrary, our data on the oxyprolin content partly in female breast and male thigh muscles contradicts the findings of Barroeta (2007) who noticed that the composition of the feed has no influence on the amino acid content in poultry meat and also do not agree with the results of Leikus et al (2004); Leikus (2006);and Juodka et al (2016) who indicated that the use of lupine or peas in the feed had no effect on the oxyprolin content in meat.…”
Section: Effects Of Different Amounts Of Blue Lupine (L Angustifoliucontrasting
confidence: 57%
“…Duck is an alternative to the widespread use of chicken and turkey. The studies by Qiao et al (2002), Wawro et al (2004), Galal et al (2011) and Juodka et al (2016) indicated that the content of intramuscular fat in the breast muscles of ducks is higher than that of chicken and turkey meat. Different intramuscular fatty acids have a different influence on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Duck is an alternative to the widespread use of chicken and turkey. Fat content of intramuscular in the breast muscles of ducks is higher than that of chicken and turkey meat (Juodka et al, 2016).…”
Section: Introductionmentioning
confidence: 76%